Protocol to ensure continued pediatric liver transplantation service during the COVID pandemic and the encouraging outcomes. (11th March 2021) - Varma, Sharat; Pandey, Yuktansh; Chikkala, Bhargava Ram; Acharya, Rajgopal; Verma, Sapana; B, Inbaraj; Sreekumar, Sreejith; Das, Dibyajyoti; Dey, Rajesh; Agarwal, Shaleen; Gupta, Subhash
Abstract: Coronavirus disease 2019 is a global pandemic, and to deal with the unexpected, enormous burden on healthcare system, liver transplantation (LT) services have been suspended in many centers. Development of robust and successful protocols in preventing the disease among the recipients, donors and healthcare workers would help in re‐starting the LT programs. We adapted a protocol at our center, which is predominantly a living donor liver transplant center based in north India, and continued the service as the pandemic unfolded and peaked in India with good results and shared the experience of the same. Between March 24 and June 7, 2020, during the government‐enforced public curfew—"lockdown"—7 children received LT. The protocols of infection control were drafted in our team by local customization of published guidelines. The number of pediatric LT done during the lockdown period in 2020 was similar to that done in corresponding pre‐COVID period in 2019. The outcomes were of 100% survival, and none of recipients developed COVID. One potential donor was asymptomatic positive for COVID, responded well to conservative treatment, and was later accepted as a donor. LT program during the COVID pandemic can successfully function after putting in place standard protocols for infection control. These can be implemented with minimal extra involvement of healthcare infrastructure, hence without diversion of resources from COVID management. In conclusion, pediatric liver transplantation services can be continued amid COVID‐19 pandemic after establishing a properly observed protocol with minimum additional resources.